Specific and non-specific interactions of ParB with DNA: implications for chromosome segregation - Taylor, James A. (Nucleic Acids Res, 2015)
The segregation of many bacterial chromosomes is dependent on the interactions of ParB proteins with centromere-like DNA sequences called parS that are located close to the origin of replication. In this work, we have investigated the binding of Bacillus subtilis ParB to DNA in vitro using a variety of biochemical and biophysical techniques. We observe tight and specific binding of a ParB homodimer to the parS sequence. Binding of ParB to non-specific DNA is more complex and displays apparent positive co-operativity that is associated with the formation of larger, poorly defined, nucleoprotein complexes. Experiments with magnetic tweezers demonstrate that non-specific binding leads to DNA condensation that is reversible by protein unbinding or force. The condensed DNA structure is not well ordered and we infer that it is formed by many looping interactions between neighbouring DNA segments. Consistent with this view, ParB is also able to stabilize writhe in single supercoiled DNA molecules and to bridge segments from two different DNA molecules in trans. The experiments provide no evidence for the promotion of non-specific DNA binding and/or condensation events by the presence of parS sequences. The implications of these observations for chromosome segregation are discussed.